2017
DOI: 10.18203/2320-6012.ijrms20175712
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile and the outcome of corrosive injury of GI tract

Abstract: Background: Corrosive substances are common household substances that can be ingested either accidentally or intentionally with suicidal intent. The present study was conducted to analyse the clinical profile of 50 cases of corrosive injury of GI tract and to analyse the outcome of 50 cases of corrosive injury of GI tract.Methods: The Cross-sectional study was conducted on 50 cases admitted in the toxicology ward in Rajiv Gandhi Government General Hospital, madras medical college, Chennai over a period of six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 3 publications
3
3
0
Order By: Relevance
“…Mean duration forperforming the endoscopy was 18.04±2.23 hours. Similar findings were reported by Velayudham R et al 15 in their study. They also reported almost similar mean endoscopic time of 14.06±3.48 hours.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Mean duration forperforming the endoscopy was 18.04±2.23 hours. Similar findings were reported by Velayudham R et al 15 in their study. They also reported almost similar mean endoscopic time of 14.06±3.48 hours.…”
Section: Discussionsupporting
confidence: 92%
“…There was no significant difference in the outcome among different age groups (p value >0.05). Similar mean age, age range and male dominance was reported by Arulmurugan C et al 13 , Lakshmi CP et al 14 and Velayudham R et al 15 in their study. In the present study pain was most common 33 oropharyngeal finding then salivation in 31 cases, dysphagia was most common 27 , odynophagia 15 esophageal finding and epigastric pain 20 was most commonly seen gastric finding in this study.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The present study was carried out in 31 (41%) males and 45 (59%) females, therefore the study findings by Velayudham et al are somewhat different as the higher incidence of corrosive ingestion was found to be more in males with a ratio of 2.5:1. 9 The patients were mostly young with mean age of 28.8 (range 15-65) years. The present study was supported by Velayudham et al in which the mean age was found to be 32.88±12.74 years.…”
Section: Discussionmentioning
confidence: 99%